A New Wireless Generation Technology for Video Streaming - Sarmad K. Ibrahim; Nasser N. Khamiss (Journal of Computer Networks and Communications)
With the exponential rise in the volumes of video traffic in cellular networks, there is an urgent need for improving the quality of video delivery. This research proposes a mobile generation model based on the updated technologies of the fourth- and fifth-generation mobile systems, which is called Proposed Generation (Pro-G). This model uses wider bandwidth and advanced adaptive modulation and coding. It also incorporates the method of the adaptive video streaming of multiple video data rates by using the transcoding technique, which is called H.265 proposed (H.265 pro). Thus, both methods are tested to provide a large number of users of video/data application with more speed and best quality. A comparison with 4G technology is done to assign the development regarding number of users with data rate. The suggested video coding shows how much the overall system is more reliable over the congested channel than conventional video coding technologies such as high-efficiency video coding (HEVC/H.265) and advanced video coding (AVC/H.264). The results showed that the proposed method of transmitting wireless data is better than the LTE-ADV method. In this method, the rate of data transfer increases by 29% compared with LTE-ADV, while the bit rate saving was increased to 13% in the proposed video coding compared with that in the H.265.